Investigation of phytochemical contents and anticancer, antioxidant, antimicrobial activities of Cucurbita pepo leaves - Saeed, Lara; Temüz, Mehmet Mürşit; Keser, Serhat; İnci, Şule; Dalkılıç, Lütfiye Kadıoğlu; Karatepe, Arzu (Niyazi BULUT, 2024)
Ethanol and acetone extracts of Cucurbita pepo leaves were in vitro analyzed to determine the vitamin contents, antioxidant, anticancer, and antimicrobial activity of the leaves. According to HPLC analyses, the leaves contained slight amounts of vitamin C, A, and E. The analysis for antioxidant activity revealed that both ethanol and acetone extracts exhibited high activity values against ABTS+•, OH•, and DPPH• radicals. The total phenols and flavonoid assay revealed high values for the extracts. The MTT test revealed that both ethanol and acetone extracts exhibited cytotoxic activity toward human breast cancer cells (MCF-7). But no significant activities observed against hepatocellular carcinoma cells (HepG-2). The antimicrobial activity assay revealed activity of the extracts towards selected Gram's positive and Gram's negative bacteria. These results have provided scientific motivation to use Cucurbita pepo leaves as a medicinal plant to treat oxidative and inflammatory-related diseases.
Keywords: Biochemistry and Cell Biology (Other); Biyokimya ve Hücre Biyolojisi (Diğer)